1999
DOI: 10.1053/hn.1999.v121.a98754
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Cerebrospinal Fluid Rhinorrhea Repair: Is a Lumbar Drain Necessary?

Abstract: A lumbar drain is not routinely necessary for successful closure of CSF rhinorrhea of any size. Smaller dural defects may be safely performed on an outpatient basis without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
1
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(205 citation statements)
references
References 12 publications
10
185
1
9
Order By: Relevance
“…72,80 Various authors have successfully used different types of autologous and nonautologous grafts, such as a mucoperiosteal flap from the middle turbinate or septum or mucoperichondrial, osseous, cartilaginous, fat, muscular fascia, middle turbinate, or septum pedunculated graft, or any combination of these grafts. 1,3,11,13,15,22,[24][25][26]28,35,47,51,55,56,64,65,67,77,79,90,101,108 Another widely discussed issue in endoscopic transnasal repair is whether the grafts used for repair should be placed above (inlay) or beneath (onlay) the skull base defects. In a meta-analysis, Hegazy et al 53 found that both techniques yielded similar results.…”
Section: Surgical Managementmentioning
confidence: 99%
“…72,80 Various authors have successfully used different types of autologous and nonautologous grafts, such as a mucoperiosteal flap from the middle turbinate or septum or mucoperichondrial, osseous, cartilaginous, fat, muscular fascia, middle turbinate, or septum pedunculated graft, or any combination of these grafts. 1,3,11,13,15,22,[24][25][26]28,35,47,51,55,56,64,65,67,77,79,90,101,108 Another widely discussed issue in endoscopic transnasal repair is whether the grafts used for repair should be placed above (inlay) or beneath (onlay) the skull base defects. In a meta-analysis, Hegazy et al 53 found that both techniques yielded similar results.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Spontaneous CSF leak might also occur secondary to focal atrophy of the olfactory nerve in the region of the cribriform plate. Additionally, defective development of the bony skull base could allow the arachnoid and brain tissue to protrude through the nose [14]. Spontaneous CSF leaks are idiopathic in nature; however, recent evidence has led us to realize that spontaneous CSF rhinorrhea is in reality secondary to an intracranial process, namely elevated intracranial pressure (ICP) as well as with factors such as sneezing, coughing, or other causes of normal fluctuations in cerebrospinal fluid pressure [15].…”
Section: Discussionmentioning
confidence: 99%
“…Следует учитывать не только ожидаемую пользу, но и риск осложнений, пролонгацию по-стельного режима и срока госпитализации [59].…”
Section: роль временного наружного дренирования люмбального ликвораunclassified